Adverse Drug Reaction Monitoring of Anticancer Drugs in Hematology Department - Roohi, Ghazal; Selvam R, Panner; Najari, Fares (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Cancer is among the leading causes of mortality in India. Studies have reported antineoplastic agents as the common class of drugs causing Adverse Drug Reactions (ADRs). The present study aimed to conduct active surveillance of ADRs of anticancer drugs in the hematology department. Methods: A prospective observational study was conducted in 136 patients with cancer and the incidence and frequency of ADRs were assessed. The study was conducted in 6 months in a multispecialty hospital. Results: Among 136 cancer patients, All was more prevalent (39.70%); CLL, Non- Hodgkin’s Lymphoma were less prevalent (0.73%). ADRs were more prevalent in the Pediatrics department, i.e., 18.53% of ADRs were observed in patients aged <10 years. ADRs in male patients constituted 54.39%, whereas it was 45.60% in female patients. Cytarabine caused the highest number of ADRs (34.48%). The most prevalent ADR was anemia (25.60%). Conclusion: Multiple ADRs were detected in cancer patients. We found that hematological ADRs were more prevalent. Most of the ADRs were possible reactions according to Naranjo and the World Health Organization (WHO) scales.